1964
DOI: 10.1172/jci104932
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Transport and Metabolism of Conjugated Bile Salts by Intestinal Mucosa *

Abstract: Bile salts have a central role in the digestion and absorption of fat in the intestinal tract. In addition, since the sterol nucleus is not further metabolized by mammalian cells, the bile salts represent the main excretory products of the body's cholesterol stores (1). The enterohepatic circulation of bile salts is well established, and upwards of 959 of the amount excreted through the bile duct is absorbed from the intestine for subsequent re-excretion by the liver (2). In vitro studies have shown an active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

1966
1966
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(27 citation statements)
references
References 37 publications
1
24
2
Order By: Relevance
“…DISCUSSION Despite considerable variation in the fractional turnover rates of both steroid and amino acid moieties among subjects, glycine degradation (and synthesis) was more rapid than cholic acid loss and 7-dehydroxylation in each subject. Cleavage of the amide bond of cholylglycine is mediated exclusively by bacterial enzymes (13)(14)(15)(16), but the site of such bacterial deconjugation was not indicated by this study.…”
Section: ----I ---------------I ----contrasting
confidence: 57%
“…DISCUSSION Despite considerable variation in the fractional turnover rates of both steroid and amino acid moieties among subjects, glycine degradation (and synthesis) was more rapid than cholic acid loss and 7-dehydroxylation in each subject. Cleavage of the amide bond of cholylglycine is mediated exclusively by bacterial enzymes (13)(14)(15)(16), but the site of such bacterial deconjugation was not indicated by this study.…”
Section: ----I ---------------I ----contrasting
confidence: 57%
“…As shown by previous investigators (2,3,5), experiments in this laboratory using everted gut 7.00) solutions of these sacs (3). In the case of taurocholate only ionic diffusion would be expected, whereas with cholate the low pH of the serosal solution would allow both ionic and nonionic diffusion to take place.…”
Section: Resultsmentioning
confidence: 62%
“…Other investigators (2,3,5,(15)(16)(17) have shown that only segments taken from the terminal half of the intestine are capable of transporting taurocholate and cholate against concentration gradients. However, it should be emphasized that this observation alone does not constitute proof of active transport.…”
Section: Discussionmentioning
confidence: 99%
“…The absorption of taurocholate was studied in adult and fetal everted gut rings and sacs (19,20 Thtus, the ileal mechanism for active bile salt transport is not demonstrable in the near-term fetal dog, althouigh bile salt is passively absorbed from both fetal jejtuntum and ileuim. An enterohepatic circulation of bile salt is directly demonstrable in the dog.…”
Section: Analytical Proceduresmentioning
confidence: 99%